Total Quality Management And Hotel Employee Creative Performance: The Mediation Role Of Job Embeddedment - Faraj, Kawa Mohammed; Faeq, Dalia Khalid; Abdulla, Daroon F.; Ali, Bayad Jamal; Sadq, Zana Majed (The journal of contemporary issues in business and government, 2021)
Underpinned by social exchange and JE theory, this study proposes and tests a research model that investigates the effect of TQM on FHE’screative performance mediating by JE. The data come from FHE’s who work in five star hotels in northern Iraq. The structure equation modelling results revealed that JE is the underlying mechanism through which TQM manifested by the top-management, empowerment, training, reward and teamwork practice, is linked to the FHE’s CP. The empirical data support all hypothesis and research model we have proposed is practical. The results have important implications about FHE’s of TQM practice and aforesaid.